Mortalidad y atención integral de pacientes viviendo con VIH/Sida durante la pandemia de Covid-19 en un hospital público de Loreto 2018-2021 - Lazarte Rengifo, Gerson Rafael (2024)
Objective: To determine the association between mortality and comprehensive care of patients living with HIV/AIDS during the COVID-19 pandemic at the Loreto Regional Hospital of Loreto during the period 2018 to 2021. Methods: Observational, cross-sectional, descriptive, retrospective and correlational design study. A review of the medical records of people living with Acquired Immunodeficiency Virus/AIDS (PLWHA) from the Loreto Regional Hospital who died during 2018 to 2021 was performed. The analysis was performed through SPSS v26 using descriptive statistics and Fisher's exact test with significance p40000 copRNA/mm3 (35.1%) and no TB co-infection (84.2%). In addition, they initiated antiretroviral treatment from 0 to 4 years (86%), with treatment abandonment (50.9%) and alternative treatment scheme (59.6%). Sex (p=0.041) and treatment dropout (p=0.022) were found to have significant association to mortality in PLWHA.